The challenge of the new millennium: Holmes Rolston III asks whether reasoned behaviour is possible in the midst of self-seeking ideologies and ancient appetites - Rolston, Holmes, 1932-2025, author; The Philosophers' Magazine, publisher (Colorado State University. Libraries, 2012)
The biological sciences have developed dramatically in the last half century, raising concerns about their implications for human nature and behavior. While such research can and ought to shape policy, policy equally should critique such research. Science, as much as any other human institution, needs its humanist critics--ethicists, philosophers, theologians, policymakers. We analyze a half-dozen claims coming from biological sciences hoping to demonstrate that half-truths, if taken for the whole, can be both misleading and dangerous. Fortunately scientists are also good at being their own critics. 1. Selfish genes. 2. Genetic destiny. 3. Pleistocene appetites. 4. Monkey's mind. 5. Neuroscience: Bottom up? Top down? 6. Enlightening/escalating self-interest. 7. Ideology: Reasoned governing behavior.
Keywords: genes and behavior; science policy; half-truths; bioscience; human behavior; neuroscience; science and values; governing science